The effect of Chinese construction companies on the Namibian construction industry; a construction and design team members’ perspective - Buys, Fanie; Hallick, Sean (University of the Free State, 2010)
The presence of Chinese construction companies working in Namibia has had an impact on the Namibian construction industry and the economy of the country. This article provides an overview of current trends and legislative acts relating to the construction industry in Namibia. It also describes the effect that Chinese construction companies have had on Namibian contractors and the tender opportunities available to these local contractors, and analyses to what extent Chinese construction companies comply with the various acts relating to the construction industry; as perceived by construction industry stakeholders. A questionnaire survey was conducted among Namibian contractors and building professionals and the results revealed that Chinese construction companies dominate and have a negative effect on local Small and Micro Enterprises (SMEs). Some of the Chinese contractors are being awarded tenders without having complied with the tender regulations set by the Tender Board.

Die teenwoordigheid van Chinese konstruksiemaatskappye in Namibië het ’n impak op die Namibiese konstruksiebedryf en die ekonomie van die land. Hierdie artikel gee ’n oorsig oor die stand van die konstruksiebedryf en die onderskeie wetgewings van toepasing op die Namibiese konstruksiebedryf. Dit beskryf ook die effek wat Chinese konstruksiemaatskappye op Namibiese kontrakteurs het asook op die tendergeleenthede wat aan hulle beskikbaar is; soos gesien deur betrokkenes in die konstruksiebedryf. Dit analiseer ook tot watter mate die Chinese konstruksiemaatskappye voldoen aan die vereistes van die onderskeie wette verwant aan die konstruksiebedryf. ’n Vraelysopname is onder kontrakteurs en professionele persone in die konstruksiebedryf gedoen en die resultate toon aan dat die Chinese konstruksiemaatskappye die Namibiese konstruksiebedryf domineer en ’n negatiewe uitwerking op Klein-en Mikro-Ondernemings het. Daar word verder tenders aan sommige Chinese kontrakteurs toegeken wat nie aan al die nodige tendervereistes van die Tenderraad voldoen nie.
Keywords: Chinese construction companies; Small and micro enterprises; Affirmative action; Legislation; Namibian construction industry; Chinese contractors